EL OBJETO DE (HA)SER CIENCIA EN PSICOLOGÍA - Roberto Polanco - Carrasco (CAEN, 2008)
Should we consider psychology as a science? This old question might push more than one reader away, because of the presumption that this question is out of place in front of the advances of this discipline. However, I request leniency since the objective of this editorial is to evidence that this matter has been partially approached and therefore poorly surpassed.